Deactivation of Novozym 435 during the Esterification of Ibuprofen with Ethanol: Evidences of the Detrimental Effect of the Alcohol - José, Carla (2010)
The esterification of ibuprofen using ethanol as reactant and solvent was investigated. Additionally, the surface interaction of the isomers of ibuprofen and ethanol with the biocatalyst was screened through conventional adsorption isotherms and temperature programmed surface reaction (TPSR). These investigations evidenced strong alcohol adsorption and dissolution of the biocatalyst which explains its deactivation upon reuses in the esterification reaction.